Marriage, gender and refugee migration : spousal relationships among Somali Muslims in the United Kingdom - Carver, Natasha (Politics of marriage and gender: global issues in local contexts., 2021)
This ethical and poetic ethnography analyses the upheavals to gender roles and marital relationships brought about by Somali refugee migration to the UK. Unmoored from the socio-cultural norms that made them men and women, being a refugee is described as making "everything" feel "different, mixed up, upside down." Marriage, Gender and Refugee Migration details how Somali gendered identities are contested, negotiated, and (re)produced within a framework of religious and politico-national discourses, finding that the most significant catalysts for challenging and changing harmful gender practices are a combination of the welfare system and Islamic praxis. Described as "an important and urgent monograph," this book will be a key text relevant to scholars of migration, transnational families, personal life, and gender. Written in a beautiful and accessible style, the book voices the participants with respect and compassion, and is also recommended for scholars of qualitative social research methods